A taxonomic study of the genus Bolivaritettix Günther (Orthoptera: Tetrigidae: Metrodorinae) - Deng, Wei-An; Zheng, Zhe-Min; Wei, Shi-Zhen (Zootaxa, 2010)
Taxonomy of a tetrigid genus Bolivaritettix Günther is reviewed. Two new species, B. tenuifemura sp. nov. and B. sanbaishanensis sp. nov. are described. An updated identification key to all known species of the genus is given.